Synthesis, Characterization, and Evaluation of Evaporated Casting MWCNT/Chitosan Composite Membranes for Water Desalination - Mohammed Alsuhybani; Ahmed Alshahrani; Ahmed S. Haidyrah (Journal of Chemistry)
Fresh water scarcity and pollution turn out to be a most serious issue throughout the world due to the rapid population growth. The application of nanomaterials (NMs) for the removal of pollutants from water has attracted significant attention. The nanofiltration membrane was fabricated through the evaporative casting (EC) method using multiwalled carbon nanotubes (MWCNT) and chitosan (CHIT) as the surfactant to enable water purification. The developed EC membrane properties were characterized in mechanical, surface charging (zeta potential), surface morphology, and hydrophobicity properties. Results demonstrated that incorporation of MWCNT and the biopolymers (chitosan) resulted in suitable developments in mechanical properties of the membrane. For example, the membrane has shown values for tensile strength (28 ± 1 MPa), elongation (10.2 ± 1.2%), Young’s modulus (1.2 ± 0.1 GPa), and toughness of (1.9 ± 0.2 J/g). When more significant changes were investigated on the surface morphology of the EC membrane, it was observed that the pores on the surface morphology of the EC membrane decreased as the evaporative casting method was used. Moreover, the permeability of the membrane towards water, inorganic salts, and pH effect on salt rejections was studied using the NF/RO system. These established nanocomposite membranes signify the promising candidates for fresh water desalination and elimination of organic impurities.